A new aerodynamic endonasal filtration technology for protection against pollutants and respiratory infectious agents: evaluation of the particle filtration efficacy - Saravanan, Padmanabhan; Broccolo, Francesco; Ali, Nurshahidah; Toh, Alden; Mulyana, Sakinah; Beng, Goh Lay; Imperi, Enrico; Picano, Alfredo (Frontiers in Medical Technology, 2023)
An innovative nasal filter was tested, based on aerodynamic air filtration and not on conventional air filtration by means of mesh filters. A custom testing system was designed and three sizes of the filter have been tested vs. monodispersed SiO2 particles sized 5 μm, 1 μm, and 0.5 μm under cycling flow of 6 liters per minute, provided by an artificial lung breather simulating spontaneous breathing. Accelerated testing was implemented, challenging filters with a maximum load of 200 mg per cubic meter. All three filters' sizes showed initial filtration efficiencies above 90% vs. all particles' sizes, decreased to not less than 80% after 30 min of accelerated testing, corresponding to 4.5 days of continuous use at 2 mg challenge, this value being associated with hazardous air conditions in the PSI scale. Results in this study indicate that nasal filters based on aerodynamic air filtration can provide fine and ultrafine filtration, offering protection in day-to-day life from risks associated with pollens, mites, PM, pollutants, and respiratory infectious agents, introducing acceptable respiratory resistance.